The theoretical basis of the CGIL’s analysis of the Italian economic decline - Davanzati, Guglielmo Forges; Giangrande, Nicolo (Brazilian Keynesian Review, 2019)
This paper deals with the Italian economic decline from a double perspective. First, it provides a reconstruction of the main Post Keynesian arguments explaining the bad macroeconomic performance of the Italian economy, starting from the end of the “economic miracle”. Second, it proposes a re-reading of the CGIL’s view, showing that is it consistent with a theoretical approach based on the fundamental assumptions and policy prescriptions of the Post Keynesian framework.